Local tourist willingness to pay for entrance fee in Tioman Island Marine Park, Pahang, Malaysia - Zulkepli, Zulkhairie (2020)
Tioman Island Marine Park, Pahang (TIMP) is a marine conservation area located in the South China Sea, off Pahang is about 32 nautical miles (56 km) northeast from Mersing, Johor, Malaysia. Located in the Coral Triangle area that spans from Malaysia to the Solomon Islands, TIMP is rich in marine biodiversity. This marine biodiversity attract tourists to TIMP for many years. TIMP was gazetted as Marine Park in 1998 and currently managed by Department of Marine Parks Malaysia. Since its establishment, the statistics show increasing tourists arrivals. There is only RM5 entrance fee for local tourist to TIMP, whether the foreign tourists were increase the amount to RM30 per entrance. This study is aimed to determine the entrance fee in TIMP by assessing the willingness to pay of local tourists (WTP) and come out with estimation total of entrance fee value at TIMP. In addition, the study also determined the factors influencing local tourists’ willingness to pay for entrance fee in TIMP and come out with Ordered Probit Regression analysis. Next, the study was identified the socio-demographic, visiting characteristics, and satisfaction of local tourists on quality of site of Tioman Island Marine Park and come out with descriptive analysis. Payment Card Contingent Valuation Method (CVM) was employed to elicit the values of WTP. The determination of these values directly represented the actual values of entrance fee TIMP area in Ringgit Malaysia (RM). From the monetary value, level of awareness amongst tourists towards conservation program can be illustrated. Another significant contribution is that the estimated WTP suggested a range of preferred price for entrance fee TIMP from local tourists’ perspective. Data was collected in series of face-to-face surveys. A total of 335 useable questionnaires were obtained and used in the analysis. The respondents were 18 years old and above towards tourists visited TIMP. The questionnaire comprised of four main structures which were visitation characteristic, measurement of satisfaction site quality level, WTP and sociodemography. Using the Payment Card Choice format, twelve level of bids amount were provided. The Ordered Probit Regression analysis was conducted to determine the WTP model values by using the syllabic abbreviation (STATA). The findings of the Ordered Probit Regression analysis found 6 variables significantly influencing the values of WTP. The findings of the analysis showed that, most of the local tourists are willing to pay for the entrance fee based on 6 dimensions. There are (mean local tourist satisfaction), (marital status), (self employed), (income), (mid education) and (high education). The WTP entrance fee in TIMP is RM15.156 per person/ visit/year. From this, it was found that, most of the TIMP tourists were concerned on marine conservation program. Otherwise, this showed that the local tourists were willing to pay to maintain the quality of natural resources in TIMP. The findings of this study will be useful for the park management to make decision on the applicable of entrance fee in TIMP. Other than that, it will help the park management to improve the quality of managing natural resources and also to control tourists’ behaviour in TIMP area.